Gender and sexual identity-based inequalities in adolescent wellbeing: findings from the #BeeWell Study - Jose Marquez; Neil Humphrey; Louise Black; Megan Cutts; Devi Khanna (BMC, 2023)
Abstract Background Gender and sexual minority adolescents experience greater symptoms of psychological distress than their peers, but little is known about broader aspects of their wellbeing. This study examines wellbeing inequalities relating to gender and sexual identity among adolescents from Greater Manchester in the United Kingdom. Method 37,978 adolescents (aged 12-15, attending 165 secondary schools) completed surveys of life satisfaction, positive and negative affect (hedonic framework); autonomy, self-esteem, optimism, and positive relationships (eudaimonic framework); and, symptoms of distress and mental wellbeing (complete state framework). Structural correlated factors models were used to assess gender and sexual identity wellbeing inequalities. Results The magnitude of wellbeing inequalities pertaining to gender and sexual identity were routinely substantially greater than those concerning other characteristics (e.g., socio-economic disadvantage). Gender identity wellbeing inequalities followed a consistent pattern, with the largest disparities evident between gender diverse adolescents and boys. Sexual identity wellbeing inequalities also followed a consistent pattern, with the largest disparities evident between sexual minority youth (both gay/lesbian and bi/pansexual) and their heterosexual peers. Finally, variation was evident across wellbeing domains. For example, observed gender identity (boys vs. girls) and sexual identity (heterosexual vs. sexual minority) disparities were substantially greater for symptoms of distress than for mental wellbeing in the complete state model. Conclusions LGBTQ + adolescents experience lower wellbeing than their peers, and this is evident across a range of wellbeing domains. Accordingly, there is an urgent need for the prioritisation of improved prevention and intervention efforts that can better meet the needs of gender diverse and sexual minority youth, and future research should be conducted to improve understanding of the mechanisms underpinning the wellbeing inequalities observed.